2019
DOI: 10.1186/s12887-019-1566-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allopurinol in addition to hypothermia treatment in neonates for hypoxic-ischemic brain injury on neurocognitive outcome (ALBINO): study protocol of a blinded randomized placebo-controlled parallel group multicenter trial for superiority (phase III)

Abstract: Background Perinatal asphyxia and resulting hypoxic-ischemic encephalopathy is a major cause of death and long-term disability in term born neonates. Up to 20,000 infants each year are affected by HIE in Europe and even more in regions with lower level of perinatal care. The only established therapy to improve outcome in these infants is therapeutic hypothermia. Allopurinol is a xanthine oxidase inhibitor that reduces the production of oxygen radicals as superoxide, which contributes to secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…A second dose of either allopurinol or mannitol (both 10 mg/kg, intravenous over 10 min) was administered 12 h after the first dose in neonates who subsequently underwent TH. The primary endpoint of this study is death or severe neurodevelopmental impairment vs survival without severe neurodevelopmental impairment at the age of 2 years [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second dose of either allopurinol or mannitol (both 10 mg/kg, intravenous over 10 min) was administered 12 h after the first dose in neonates who subsequently underwent TH. The primary endpoint of this study is death or severe neurodevelopmental impairment vs survival without severe neurodevelopmental impairment at the age of 2 years [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Patients were eligible for the ALBINO trial if they fulfilled at least one of the perinatal asphyxia criteria: (1) pH < 7 or base deficit ≥ 16 mmol/L, (2) need for ongoing cardiac massage for ≥ 5 min postpartum; (3) need for adrenalin administration during resuscitation; and (4) Apgar score ≤ 5 after 10 min postpartum; in combination with two or more early signs of evolving encephalopathy: (1) altered state of consciousness; (2) hypotonia or hypertonia; (3) absent/insufficient spontaneous respiration requiring respiratory support for at least 10 min postpartum; and (4) abnormal primitive reflexes/abnormal movements (i.e., seizures). Further details of the study protocol have been published [ 12 ]. The most important exclusion criteria were a gestational age < 36 weeks, an estimated birth weight < 2500 g, or severe congenital abnormalities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doycheva et al [ 30 ] demonstrated that G-CSF + Ab improved body weight, reduced brain tissue damage, and improved long-term neurological function when assessed at 96 h and 5 weeks post HI in the neonatal rat pups, as well as conferring greater neuroprotection by depleting neutrophil accumulation, while G-CSF + metyrapone treatment not only lower caspase-3 expression level but also reduce corticosterone levels in neonates after HI injury [ 89 ]. Surprisingly, there has not been any study evaluating combinational therapy of G-CSF and therapeutic hypothermia (TH), as other modalities have been tried and underwent and/or are undergoing clinical trials in neonatal HIE, such as with epo and TH [ 120 122 ], xenon and TH [ 51 , 123 , 124 ], melatonin and TH [ 46 , 47 ], and allopurinol and TH [ 125 ]. Thus, more study is needed to explore and evaluate the neuroprotective effect of G-CSF in combination with therapeutic hypothermia as well as other emerging agents.…”
Section: Combinational Therapy With Other Agentsmentioning
confidence: 99%
“…In particular, it was recently demonstrated in animal experiments that these drugs confer neuroprotection against cerebral ischemia, by activating several mechanisms that involve both anti-oxidant and anti-inflammatory effects (25,26). Most importantly, the therapeutic potential of pioglitazone has been shown in patients after ischemic stroke or transient ischemic attack events (27) and allopurinol has been recently tested in neonates for HIE (28). In addition, the beneficial action of pioglitazone was also evidentiated in models of spinal cord injury (29) and amyotrophic lateral sclerosis (30), demonstrating their neuroprotective effect.…”
Section: Introductionmentioning
confidence: 99%